Analisis Perlindungan Hukum Terhadap Kepemilikan Hak Atas Tanah Bagi Kepentingan Umum - Julianti Sembiring; Ramsul Nababan; Putri Juliani Br Tarigan; Octa Vioni Pinem; Rizal Sanusi Hasibuan (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to analyze legal protection for ownership of land rights for the public interest, and this research can be useful as a reference for readers. This research uses a qualitative descriptive research method, with a type of normative legal research - empirical or literature. Sugiyono said that quantitative research is a method used to examine the condition of natural objects where the researcher is the key instrument. type of normative-empirical legal research according to Muhaimin in his book entitled: Legal Research Methods says that normative-empirical legal research is